Natriuretic peptides, nitrite/nitrate and superoxide dismutase have additional value on top of the GRACE score in prediction of one-year mortality and rehospitalisation for heart failure in STEMI patients — Multiple biomarkers prospective cohort study. (15th May 2016) - Parenica, Jiri; Kala, Petr; Pavkova, Monika Goldbergova; Tomandl, Josef; Spinar, Jindrich; Littnerova, Simona; Jarkovsky, Jiri; Mebazaa, Alexandre; Tomandlova, Marie; Dastych, Milan; Gottwaldova, Jana; Gayat, Etienne
Abstract: Background: Blood-based biomarkers have a prognostic value in patients with myocardial infarction. The aim of our prospective observational cohort study was to evaluate the prognostic value of biomarkers of different pathophysiological pathways for the occurrence of 1-year all-cause mortality and hospitalisation due to acute heart failure. Methods and results: In 593 patients with ST-segment elevation MI (STEMI) treated by primary PCI, biomarkers were evaluated at 24 h after MI onset. A minimum of three-year follow-up was achieved in all patients. The combination of 1-year all-cause mortality and hospitalisation due to heart failure was the primary endpoint. A cohort for validation of our combined GRACE–natriuretic peptide (NP) score included 667 STEMI patients. The primary endpoint was reached in 9.3% of patients. Among 21 biomarkers, only B-type natriuretic peptide (BNP), NT-proBNP, superoxide dismutase and nitrite/nitrate, added to clinical GRACE score led to a significant increase in the area under the curve of C statistics, in comparison to GRACE alone (tested by Delong's test). Continuous net reclassification improvement and integrated discrimination index demonstrated an improved reclassification and discrimination of the GRACE model for SOD, BNP and NT-proBNP, and improved reclassification for nitrite/nitrate. Consistent results for this new combined prognostic model GRACE–NP were found also for a validation cohort. Conclusions: The levels of NP have an additional value to the prognostic properties of the GRACE score for the prediction of the combined endpoint of one-year mortality or hospitalisation for AHF. Nitrite/nitrate and SOD are strong prognostic factors, even on top of the GRACE score.